Strategi Digital Marketing Melalui Media Sosial Instagram Pada PT. Anugerah Santosa Abadi Di Surabaya - Yunita Sari; Jojok Dwiridotjahtjono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One of the marketing tools that contribute to the success of sales promotion is digital marketing through social media. The purpose of this scientific article is to understand how Instagram social media content management functions as a digital marketing strategy at PT Anugerah Santosa Abadi. The method used is descriptive method, with data sources coming from documents, observations, and interviews. PT Anugerah Santosa Abadi implements a digital marketing strategy that includes research, content creation, promotion, and analysis of the results of digital marketing efforts. The results of this digital marketing strategy show that PT. Anugerah Santosa Abadi managed to effectively increase its marketing reach and performance through the Instagram digital platform.